ДИСТАНЦИОННОЕ ИЗМЕРЕНИЕ ЭЛЕКТРИЧЕСКИХ ПАРАМЕТРОВ ВЫСОКОВОЛЬТНОЙ ИЗОЛЯЦИИ ПОД РАБОЧИМ НАПРЯЖЕНИЕМ - Борщев, П.И. (Інститут електродинаміки НАН України, Київ, 2015)
A system for measuring the electric parameters of high-voltage insulation under operating voltage, consisting of a central unit and measuring modules to be placed in close proximity to objects. Synchronization of the modules is performed by the receivers of signals of global positioning systems. Distribution of information processing functions between the modules of the system will reduce the amount and speed of information exchange and as a result to abandon the use of long cables. Metrological characteristics of the system correspond to the best known examples. References 10, figures 2